2017
DOI: 10.1016/j.biochi.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of long non-coding RNA in gallbladder cancer pathogenesis

Abstract: Gallbladder cancer (GBC) is the most common and aggressive form of biliary tract carcinoma with an alarmingly low 5-year survival rate. Despite its high mortality rate, the underlying mechanisms of GBC pathogenesis are not completely understood. Recently, from a growing volume of literature, long non-coding RNAs (lncRNAs) have emerged as key regulators of gene expression and appear to play vital roles in many human cancers. To date, a number of lncRNAs have been implicated in GBC, but their potential roles in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 75 publications
0
21
0
Order By: Relevance
“…During the last few years, more and more studies have found a connection between BTC and lncRNAs [17]. As summarized in Figure 1A and Table 1, most lncRNAs described in BTC might have an oncogenic role, as they are overexpressed in BTC patient specimens compared to non-tumor tissue and their enhanced expression correlates with unfavorable clinical characteristics (see Figure 2).…”
Section: Lncrnas In Biliary Tract Cancermentioning
confidence: 98%
See 2 more Smart Citations
“…During the last few years, more and more studies have found a connection between BTC and lncRNAs [17]. As summarized in Figure 1A and Table 1, most lncRNAs described in BTC might have an oncogenic role, as they are overexpressed in BTC patient specimens compared to non-tumor tissue and their enhanced expression correlates with unfavorable clinical characteristics (see Figure 2).…”
Section: Lncrnas In Biliary Tract Cancermentioning
confidence: 98%
“…The lack of efficient therapeutic options and the high mortality rates demand for a better understanding of the underlying molecular mechanisms of BTC development and progression [16]. Recent studies suggest that long non-coding RNAs (lncRNAs) might be essentially involved in tumorigenesis via different molecular mechanisms [17].…”
Section: Biliary Tract Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The prognosis of GC remains poor due to tumor metastasis and recurrence and the potential underlying factors, including the heterogeneity in the functions of key genes and interlink signaling molecules and regulatory networks involved in the initiation, progression and invasion of GC (2,3). In this regard, the role of regulatory molecules in the tumor microenvironment such as long non-coding RNAs (lncRNAs), microRNAs (miRNAs), and other non-coding RNAs (ncRNAs) has been scrutinized, and recent ndings have shown that lncRNAs play important roles in a wide range of physiological and pathophysiological processes, and act as oncogenes or tumor suppressor genes in tumorigenesis and cancer metastasis (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…It has been well-established that long (> 200nt) non-coding RNAs (lncRNAs) contribute signi cantly to the development and progression of GBC [7]. Different from mRNAs as the template for the synthesis of proteins, lncRNAs participate in cancer biology mainly by regulating the expression of certain oncogenes and tumor suppressors [8,9].…”
Section: Introductionmentioning
confidence: 99%